WORKING PAPER FOR PREPARATION OF FUNDS STATEMENT. - Gustafson, George A. (The Accounting Review, 1964)
Abstract This article is a discussion which is a continuation of the article entitled, Working Paper for Preparation of Cash-Flow Statement, published in the January 1963 issue of the journal, the Accounting Review. The same comparative data, operating detail, and supplementary data has been used for illustrative purposes. In addition, the funds statement and cash-flow statement will be compared to show the relationships between the components of the two statements. The funds statement, known by other titles such as the source and application of funds statement and statement of application of funds, as conventionally prepared, is an analysis of working capital. It is generally accompanied by a schedule of the items making up the working capital, which by definition is the difference between current assets and current liabilities. Current assets and current liabilities are regarded as the funds, that is, working capital, and it is the purpose of the funds statement to describe the causes for the total change in the working capital for the reporting period such as a month, a year, and so on.